Effect of Surface Roughness on Characteristics of Textured Hydrodynamic Bearings - Hongtao Wang; Shaolin Zhang; Shuai Yang (Jixie chuandong)
For a radial hydrodynamic bearing with surface micro texture，the Gauss random rough surface is used to simulate the surface roughness of the bearing bush. A mathematical model of bearing oil film characteristics is established under the coupling of surface micro texture and roughness. On this basis，the static and dynamic characteristic parameters under different eccentricities and speeds are calculated and the influence of the surface roughness on the pressure distribution and instability threshold speed of textured hydrodynamic bearings are analyzed. The results show that the proper surface roughness can improve the oil film pressure and bearing capacity under certain eccentricities，the friction force and average temperature rise also increase，and the instability speed of textured hydrodynamic bearing decreases due to roughness. The theoretical results are compared with the test results of the M2000 friction and wear testing machine to verify the rationality of the model. The research has certain reference significance for the study of the lubrication mechanism of sliding bearings that take into account both roughness and texture.